2018
DOI: 10.1080/00224545.2018.1441795
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social status and the components of agency

Abstract: Building on the two fundamental dimensions of social judgment distinguishing communion from agency, the purpose of the present work was to show that the strength of the relationship between social status and agency depends on specific components at issue: assertiveness, competence, and effort. Four experimental studies were conducted using two complementary paradigms. In Studies 1 and 2, we manipulated social status, and participants had to rate the target on competence, assertiveness, and effort. In Studies 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 49 publications
8
38
0
Order By: Relevance
“…Framing competence as effort (vs. talent) led to higher perceived warmth, which mediated the effect of competence framing on brand outcomes. This competence sub‐dimension having different relations with warmth replicates earlier work in social psychology (Louvet et al, 2019).…”
Section: Service Marketingsupporting
confidence: 85%
“…Framing competence as effort (vs. talent) led to higher perceived warmth, which mediated the effect of competence framing on brand outcomes. This competence sub‐dimension having different relations with warmth replicates earlier work in social psychology (Louvet et al, 2019).…”
Section: Service Marketingsupporting
confidence: 85%
“…Aggressive interactions can lead to a social hierarchy and influence behavior and physiology in vertebrates from teleost to mammals [1][2][3][4][5]. A general behavioral inhibition can cause appetite suppression, reduction of reproductive behavior, and low spontaneous locomotor activities, particularly in subordinate individuals when a social hierarchy exists in an animal population such as arctic charr (Salvelinus alpinus) and tree shrews (Tupaiidea) [6][7][8][9]. On the other hand, the levels of the monoamine neurotransmitter serotonin (5-hydroxytryptamine, 5-HT) and dopamine (DA) are related to the level of social stress in many species [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has, for example, shown that trustworthiness (morality) is even more important than friendliness (warmth) for positive other-evaluation (Abele and Hauke 2020;Brambilla and Leach 2014), but still both communal facets are positively related to it. Likewise, previous research has shown that assertiveness is even more important than competence for positive self-esteem (Abele et al 2016;Hauke and Abele 2020a, b) or for status perception (Carrier et al 2014;Louvet et al 2019), but still both agentic facets are positively related to them. Contrasting effects in opposing directions for two facets of the same basic dimension have been discussed theoretically, but have rarely been shown empirically.…”
Section: Implications For Social Perception Researchmentioning
confidence: 81%
“…Regarding communion, research has shown that morality plays a more central role in the evaluation of groups and individuals than warmth (Abele and Hauke 2019;Abele 2019, 2020a, b;Leach et al 2007;review: Brambilla and Leach 2014). Regarding agency, first empirical evidence shows that ascribed status is more related to assertiveness than to competence (Carrier et al 2014;Louvet et al 2019) as is self-esteem (Abele et al 2016;Hauke and Abele 2020a, b). In short, communion and agency with their two facets each have proven to be a useful conceptualization of how we perceive others.…”
Section: Basic Dimensions Of Social Perception: Communion and Agencymentioning
confidence: 99%